SIMULATION MODELS FOR USE IN THE LEARNING PROCESS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article highlights the importance and effectiveness of using simulation models in the educational process. Simulation models allow students to consolidate theoretical knowledge with practical experience, make decisions in real conditions, and model various situations. In fields such as engineering, medicine, economics, and linguistics, such models help make the educational process interactive and effective. The article also discusses the process of implementing simulation models, their advantages, and future development prospects.